2022
DOI: 10.3389/fpls.2021.788433
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candidate Forage Yield Genes in Sorghum (Sorghum bicolor L.) Using Integrated Genome-Wide Association Studies and RNA-Seq

Abstract: Genetic dissection of forage yield traits is critical to the development of sorghum as a forage crop. In the present study, association mapping was performed with 85,585 SNP markers on four forage yield traits, namely plant height (PH), tiller number (TN), stem diameter (SD), and fresh weight per plant (FW) among 245 sorghum accessions evaluated in four environments. A total of 338 SNPs or quantitative trait nucleotides (QTNs) were associated with the four traits, and 21 of these QTNs were detected in at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Many previous studies have proven that the integrated analysis of GWAS and RNA-seq is useful in detecting candidate genes of complex traits ( Yuan et al., 2019 ; Wang et al., 2022 ; He et al., 2022 ). For example, eight candidate genes were identified for tolerance to salt stress in Alfalfa by GWAS coupled with transcriptome analysis ( He et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies have proven that the integrated analysis of GWAS and RNA-seq is useful in detecting candidate genes of complex traits ( Yuan et al., 2019 ; Wang et al., 2022 ; He et al., 2022 ). For example, eight candidate genes were identified for tolerance to salt stress in Alfalfa by GWAS coupled with transcriptome analysis ( He et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, eight candidate genes were identified for tolerance to salt stress in Alfalfa by GWAS coupled with transcriptome analysis ( He et al., 2022 ). Eight candidate genes for forage yield in Sorghum were also identified by this method ( Wang et al., 2022 ). In the present study, 27 DEGs were identified by GWAS and transcriptome sequencing, of which four were significantly up-regulated under waterlogging stress and were detected in different stages.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis can provide insight into the changes in the DEGs expression level, important biological processes, and pathways (Zhang et al, 2017 ). Combining GWAS with RNA-seq can decrease the higher false-positive rate (FDR) inherent in GWAS analysis, and improve the accuracy of gene selection (Xie et al, 2019 ; Wang et al, 2022 ). However, to our knowledge, there are no relevant studies on sunflowers.…”
Section: Introductionmentioning
confidence: 99%
“…52.4 Mb, PVE: 3.1%) QTLs, respectively. Wang et al (2022a) identified two genes ( Sobic.003G047700 and Sobic.003G047800 ), both encoding cytokinin-O-glucosyltransferase 3, and Sobic.003G375100 encoding a mitochondrial DNA repair RAD52-like protein 1, as candidate genes responsible for stem diameter regulation using GWAS and RNA-seq. Since multiple mutants with thicker stems have been found in a gamma-ray-induced mutant library ( Ordonio et al 2014 , 2016 ), it is expected that the identification of the genes responsible for these mutants will provide useful information for breeding stem thickness in the future.…”
Section: Traits Related To Biomass Yieldmentioning
confidence: 99%
“…However, it is not appropriate to suggest that “this variety is perfect” because the required traits such as the presence or absence of awns and size of the glume may vary depending upon the cultivation environment. In practice, there are trade-offs among traits; for example, it is known that tiller number is negatively correlated with stem diameter in sorghum germplasms ( Wang et al 2022a ). In addition, many agronomic traits are affected by the environment, making it difficult to breed the desired variety as desired; therefore, varieties for either end use will eventually require fine-tuning based on the environment and cultivation requirements.…”
Section: Crop Ideotypesmentioning
confidence: 99%